Correlation between photorespiration, CO₂-assimilation and spatiotemporal dynamics of photosynthesis in leaves of the C₃-photosynthesis/crassulacean acid metabolism-intermediate species Clusia minor L. (Clusiaceae) - Duarte, H. M; Lüttge, U (Trees (Berlin, West), 2007)
The tree Clusia minor L. (Clusiaceae) operates with different modes of photosynthesis in response to different combinations of environmental parameters. Here plants were subjected to experimental conditions eliciting performance of C₃-photosynthesis and crassulacean acid metabolism (CAM), respectively. A combination of instruments was used to determine CO₂ and water vapour gas exchange, relative quantum use efficiency of photosynthesis (ΦPSII) and for the first time in such studies also photorespiration simultaneously with the other parameters. In the C₃-mode photorespiration was constant during the light period, where oxygenase activity of ribulose-bis-phosphate carboxylase/oxygenase (RubisCO) [graphic removed] was ranging between 32.1 and 35.7% of total RubisCO activity. In the CAM-mode photorespiration depended on the CAM phases. In phase II in the morning [graphic removed] was 15.6%. In phase IV in the afternoon initially it was 37.9% and then declined to 17.6% of total RubisCO activity towards the evening. Anatomically leaves of C. minor are differentiated in palisade and spongy parenchyma with an internal air space of 9.3% of the total volume and therefore could be structurally homobaric. However, heterogeneity of ΦPSII under both non-photorespiratory and photorespiratory conditions in the C₃- and CAM-mode indicated that lateral diffusion of CO₂ and O₂ were subject to limitations showing that leaves are functionally heterobaric.